Biocompatible MOFs with high absolute quantum yield for bioimaging in the second near infrared window. Issue 39 (30th July 2018) - Sava Gallis, Dorina F.; Butler, Kimberly S.; Rohwer, Lauren E. S.; McBride, Amber A.; Vincent, Grace; Chong, Casey V.; Pearce, Charles J.; Luk, Ting S.
Abstract : Biocompatible mixed metal YbNd metal–organic frameworks are demonstrated to be highly efficient emitters in the second NIR window. Abstract : Here we detail a study highlighting the correlation between particle size and absolute quantum yield (QY) in novel mixed metal near-infrared (NIR) emitting metal–organic frameworks (MOFs) materials. The nanoscale analogue in this series presents a QY of 6.3%, the highest of any NIR emitting MOFs reported to date.